Adsorption Analysis of Green Shells as Temperature Reducer In Coolbox - Nanang Ruhyat; Ahmad Afif (International Journal of Advanced Technology in Mechanical, Mechatronics and Materials, 2022)
: Green mussels (Perna Viridis) are a source of seafood consumed by the Indonesian people with a fairly high percentage. The high consumption rate is followed by a high amount of processing waste in the form of shells that are allowed to accumulate. Generally, waste shells are only used as handicrafts or wall decorations. In this study, green mussel shell waste (Perna Viridis) was used as an adsorbent medium to reduce air temperature, besides that, it was used to test motorcycle exhaust emissions. The test is carried out by placing the adsorbent in a cool box which is tested on the heater as a heat source with temperature variations in the control heater 80, 100, 150 and motorcycle exhaust gas with variations in engine speed of 2500 rpm, 3900 rpm, 4700 rpm. The test results on the heater show that the green mussel shells have been able to reduce the temperature by or 35% of the heat source. Furthermore, in testing the exhaust gas of the motor at 4700 rpm with a temperature of 170°C it can be reduced by or 71.48% of the heat source. In addition, the cool box is also able to reduce motorcycle exhaust emissions, especially CO2 by 2,6 %. Thus, green mussel shells can be used as an alternative medium for adsorbents